Strategi Guru PAI Dalam Membina Akhlakul Karimah Siswa - Arlina; Fauziyah, Nur; Rahayu, Putri Maymuhamnah; Nainggolan, Muhammad Afrizal; Amalia, Adila (At-Tadris: Journal of Islamic Education, 2023)
This survey was carried out to learn about the initiatives used to raise student morale in the course of akhlakul karimah. Researchers used qualitative methods with a phenomenological approach. By using this method, researchers obtained the results of interviews about their efforts to improve student morals. The researcher selected the teacher contact for this study. From the research we conducted, it is clear that any effort an educator or teacher can make to improve student morals is to set a good example, starting with the teacher and emulating by students. Efforts made by the teacher include giving lessons on reading the Qur'an and memorizing Juz 30, providing memorization related to dhuha prayers, carrying out congregational prayers, and instilling good morals in their students. This effort is made to ensure that students have good morals. The result of these efforts is that around 98% of students already reflect good morals. Efforts to improve student morals have been successful, and it can be said that many students already have good morals. However, because of the environment in which students live, this attitude does not rub off on some students.